2014
DOI: 10.1007/s10495-014-1046-4
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate affects proliferation but not survival of human colorectal cancer cells

Abstract: Dichloroacetate (DCA) is a metabolic reprogramming agent that reverses the Warburg effect, causing cancer cells to couple glycolysis to oxidative phosphorylation. This has been shown to induce apoptosis and reduce the growth of various types of cancer but not normal cells. Colorectal cancer cells HCT116, HCT116 p53(-/-), and HCT116 Bax(-/-), were treated with DCA in vitro. Response to treatment was determined by measuring PDH phosphorylation, apoptosis, proliferation, and cell cycle. Molecular changes associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
4
15
0
1
Order By: Relevance
“…Our previous study demonstrated that dichloroacetate effectively induced a dose-dependent proliferation arrest of in vitro cultures of glioblastoma cells but had no significant effect on noncancerous cells (15). This result is in line with most of the studies that investigated the efficacy of dichloroacetate demonstrating that a therapeutic window exists although suprapharmacologic level of dichloroacetate (5-50 mmol/L) is necessary to halt the growth of cancer cells in vitro (9,32,33,35). In the current study, we further analyzed the cell-cycle distribution after dichloroacetate treatment showing that dichloroacetate induced G 2 -M arrest and decreased the cell proportion in S-phase.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our previous study demonstrated that dichloroacetate effectively induced a dose-dependent proliferation arrest of in vitro cultures of glioblastoma cells but had no significant effect on noncancerous cells (15). This result is in line with most of the studies that investigated the efficacy of dichloroacetate demonstrating that a therapeutic window exists although suprapharmacologic level of dichloroacetate (5-50 mmol/L) is necessary to halt the growth of cancer cells in vitro (9,32,33,35). In the current study, we further analyzed the cell-cycle distribution after dichloroacetate treatment showing that dichloroacetate induced G 2 -M arrest and decreased the cell proportion in S-phase.…”
Section: Discussionsupporting
confidence: 75%
“…It has been demonstrated with moderate antitumor activity (31)(32)(33) and to induce apoptosis in tumors of patients with glioblastoma by restoring the mitochondrial activity (34). Several studies have also used it as a radiosensitizer in lung (11), colorectal (13), and prostate cancer cells (12) in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…4A) showed that increased proteins involved in structural constituent of ribosome, structural molecule activity, ATPase activity were changed significantly, while the decreased proteins participated in nucleic acid binding, heterocyclic compound binding, and other bindings were severely affected. The results were consistent with the notion that DCA can lead to the inhibition of cell proliferation and cause cell death24. In cellular compartment (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In the colorectal cancer cell line HCT116, DCA has been shown to affect cell proliferation without affecting survival or inducing apoptosis [65]. In other cancer cell lines, the effects were more varied [66].…”
Section: Catching Cancer In the Metabolic Crab Pot: Attempts Failurementioning
confidence: 99%